2011
DOI: 10.1155/2011/298348
|View full text |Cite
|
Sign up to set email alerts
|

KIR/HLA Interactions and Pathogen Immunity

Abstract: The innate immune system is the first line of defence in response to pathogen infection. Natural killer (NK) cells perform a vital role in this response with the ability to directly kill infected cells, produce cytokines, and cross-talk with the adaptive immune system. These effector functions are dependent on activation of NK cells which is determined by surface receptor interactions with ligands on target cells. Of these receptors, the polymorphic killer immunoglobulin-like receptors (KIRs), which interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 84 publications
0
80
1
1
Order By: Relevance
“…Full-length sequencing of KIR haplotypes showed that the framework regions divide the KIR locus into two parts: centromeric (C) and telomeric (T) segments that differ in their gene contents [5,9,10]. The centromeric part of the A haplotype contains KIR2DL3, -2DL1 and -2DP1, in addition to 3DL3 and -3DP1,while the telomeric part contains the KIR3DL1 and -2DS4 genes, in addition to KIR2DL4 and -3DL1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Full-length sequencing of KIR haplotypes showed that the framework regions divide the KIR locus into two parts: centromeric (C) and telomeric (T) segments that differ in their gene contents [5,9,10]. The centromeric part of the A haplotype contains KIR2DL3, -2DL1 and -2DP1, in addition to 3DL3 and -3DP1,while the telomeric part contains the KIR3DL1 and -2DS4 genes, in addition to KIR2DL4 and -3DL1.…”
Section: Introductionmentioning
confidence: 99%
“…The centromeric part of the A haplotype contains KIR2DL3, -2DL1 and -2DP1, in addition to 3DL3 and -3DP1,while the telomeric part contains the KIR3DL1 and -2DS4 genes, in addition to KIR2DL4 and -3DL1. Unlike the A haplotype, which is fixed, uniform and conserved, the B haplotype is polymorphic and exhibits a variable centromeric end that includes the KIR2DS2, -2DL2, -2DL5B, -2DS3 and -2DS5 genes, in addition to KIR3DL3 and -3DP1, while the telomeric part of the B haplotype contains the KIR3DS1 and -2DS1 genes, in addition to KIR2DL4 and -3DL1 [10,11]. Therefore, diversity is generated in the KIR locus by the content of group A and group B haplotype genes and the allelic variation that occurs within both the centromeric and telomeric regions [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in the ICC group profound increases were observed in KIR2DL1, KIR3DL1 and NKG2D in contrast to the 1994 CDC group. KIR2DL1 and KIR3DL1 are inhibitory receptors while NKG2D is an activating receptor, these receptors inhibit and activate NK cytotoxic activity respectively [22][23][24][25]. An increase in inhibitory receptors in the ICC group may account for the reduced cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…To date, these studies have mainly targeted viral infections such as human immunodeficiency virus infection, hepatitis C, but also cancer, autoimmune, and inflammatory disorders [29][30][31][32]. In general, activating genotypes generally appear to be beneficial during viral infections, whereas they increase the risk for susceptibility to autoimmunity [33].…”
Section: Introductionmentioning
confidence: 99%